Altered Percent Amplitude of Fluctuation in Healthy Subjects After 36 h Sleep Deprivation - Zeng, Bingliang; Zhou, Jian; Li, Zicong; Zhang, Hua; Li, Zongliang; Yu, Peng (Frontiers in Neurology, 2021)
Objective: To investigate regional brain activity alteration in healthy subjects after sleep deprivation (SD) relative to rested wakefulness using percent amplitude of fluctuation (PerAF) method. Methods: A total of twenty healthy subjects (12 males, 8 females; age, 22.25 ± 1.12 years) were recruited. All subjects underwent the MRI sessions and attention network tests twice, once was during rested wakefulness status, and the other was after 36 h SD. The PerAF method was applied to identify the SD-related regional brain activity alteration. ROC curve was used to evaluate the ability of the PerAF method in distinguishing the two-sleep status. Pearson correlation was used to determine the relationships between brain alteration and attention network test. Results: SD allowed 2.23% decrease in accuracy rate and 8.82% increase in reaction time in attention network test. SD was associated with increased PerAF differences in bilateral visual cortex and bilateral sensorimotor cortex, and decreased PerAF differences in bilateral dorsolateral prefrontal cortex and bilateral cerebellum posterior lobe. These areas revealed extremely high discriminatory power with extremely high AUC value (0.993-1) in distinguishing the two status. The accuracy rate positively correlated with bilateral cerebellum posterior lobe and bilateral dorsolateral prefrontal cortex, and negatively correlated with bilateral sensorimotor cortex. Conclusions: Acute SD could lead to approximate 8%, which was associated with increased The PerAF differences in regional brain activity may be contributed to the cognitive deficits. The PerAF could be served as a potential sensitivity biomarker to identify different sleep status.